2018
DOI: 10.1016/j.jpsychires.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dopamine signaling genes in the post-mortem brain of individuals with mental illnesses is moderated by body mass index and mediated by insulin signaling genes

Abstract: Preclinical studies implicate insulin signaling as a modulator of dopamine transmission, but human data is currently limited. We hypothesize that changes in the expression of insulin receptor-related genes in the post-mortem brain tissue of patients with mood and psychotic disorders mediate the expression of dopamine regulation-related genes. From a database containing microarray data from the post-mortem dorsolateral prefrontal cortex (dlPFC) (healthy controls [HC]: n = 209; patients: n = 321) and hippocampus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In autopsy results, decreased expression of insulin receptor‐associated signalling genes (ie, INSR, IRS1 and IRS2) resulted in genes that regulate dopamine neurotransmission in dlPFC and hippocampus (ie, DDC, TH, VMAT2, DRD1, DRD2, DRD5 and MAOB). The gene expression is reduced, which in turn leads to lower dopamine metabolism 152 . This result is basically consistent with relevant clinical data 150,153,154 …”
Section: Effect Of Insulin On Depressionsupporting
confidence: 88%
“…In autopsy results, decreased expression of insulin receptor‐associated signalling genes (ie, INSR, IRS1 and IRS2) resulted in genes that regulate dopamine neurotransmission in dlPFC and hippocampus (ie, DDC, TH, VMAT2, DRD1, DRD2, DRD5 and MAOB). The gene expression is reduced, which in turn leads to lower dopamine metabolism 152 . This result is basically consistent with relevant clinical data 150,153,154 …”
Section: Effect Of Insulin On Depressionsupporting
confidence: 88%
“…A recent study demonstrated that the knockdown of insulin receptors in astrocytes also generates anxiety and depressive-like behavior in mice, via decreased purinergic signaling and altered dopamine release (24). A recent post-mortem analysis in the brain of patients diagnosed with mental illness has observed a correlation between gene expression of proteins involved with both the dopaminergic system and the insulin signaling (25), supporting the idea that insulin could regulate the dopaminergic response. Oppositely, another report observed that deleting insulin receptors from dopaminergic neurons had no impact on anxiety or depressive-like behavior in young adult mice (26).…”
Section: Molecular Links Between Depression and Diabetesmentioning
confidence: 86%
“…These results suggest a potential interplay between BMI and molecular targets involved in the mechanism of action of this mood stabilizer. Although a link between BD and BMI has been established, the molecular mechanisms underlying this comorbidity have only recently started to be investigated and are still largely unknown 16,17 . Increasing our scarce knowledge of the factors predisposing patients with BD to develop metabolic comorbidities such as obesity and T2D would be of great importance, eventually allowing us to identify patients that could benefit from early monitoring and/or intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent review suggested that 24 genes previously associated with cardiometabolic phenotypes are also associated with mood disorders (major depressive disorder (MDD) and BD) 26 . An overview of studies previously investigating the role of genes potentially involved in both BD and obesity or T2D 16,17,21,2736 is reported in Table 1. The majority of these studies investigated variants already known to be associated with T2D or other metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%